"The legacy of thalidomide" ‐ A multidisciplinary meeting held at the University of York, United Kingdom, on September 30, 2016. Issue 4 (10th February 2017) - Newbronner, Elizabeth; Vargesson, Neil; Atkin, Karl
Abstract : Background: Between 1957 and 1962 thalidomide was used as a nonaddictive, nonbarbiturate sedative that also was successful in relieving the symptoms of morning sickness in early pregnancy. Infamously, thousands of babies were subsequently born with severe birth defects. The drug is used again, today, to successfully treat leprosy, and tragically, there is a new generation of thalidomide damaged children in Brazil. While the outward damage in babies has been documented, the effects of the damage upon the survivors as they grow up, the lifestyle changes and adaptations required to be made, as well as studies into ageing in survivors, has received little attention and remains understudied. Methods: A unique multidisciplinary meeting was organized at the University of York bringing together thalidomide survivors, clinicians, scientists, historians, and social scientists to discuss the past, the current and the future implications of thalidomide. Results: There is still much to learn from thalidomide, from its complex history and ongoing impact on peoples' lives today, to understanding its mechanism/s to aid future drug safety, to help identify new drugs retaining clinical benefit without the risk of causing embryopathy. Conclusion: For thalidomide survivors, the original impairments caused by the drug are compounded by the consequences of a lifetime of living with a rare disability, and early onset age‐related health problems. This has profound implications for their quality of life and need for health and social care services. It is vital that these issues are addressed in research, and in clinical practice if thalidomide survivors are to "age well". Birth Defects Research 109:296–299, 2017. © 2017 Wiley Periodicals, Inc.